2009
DOI: 10.2174/187153009787582423
|View full text |Cite
|
Sign up to set email alerts
|

Glucans as Biological Response Modifiers

Abstract: Beta-D-glucans belong to a group of natural, physiologically active compounds, generally called biological response modifiers. Glucans represent highly conserved structural components of cell walls in yeast, fungi, or seaweed. Despite long history of research, the exact mechanisms of glucan action remain unsolved. The present review starts with the history of glucans. Next, the detailed information about the possible glucan sources is followed by a description of the mechanisms of action. Physiological functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 74 publications
1
92
1
2
Order By: Relevance
“…They stimulate phagocytes for the production of cytokines IL-1, IL-9, TNF-α, as well as affect the synthesis of acute-phase proteins, including ceruloplasmin . Interleukin-1 stimulates T lymphocytes which in a consequence release interleukin-2, which in turn stimulates proliferation of T and B lymphocytes, natural killer (NK) and lymphokine-activated killer (LAK) cells as well as enhances the activity of natural suppressor cells and macrophages (Novak and Vetvicka 2009).…”
mentioning
confidence: 99%
“…They stimulate phagocytes for the production of cytokines IL-1, IL-9, TNF-α, as well as affect the synthesis of acute-phase proteins, including ceruloplasmin . Interleukin-1 stimulates T lymphocytes which in a consequence release interleukin-2, which in turn stimulates proliferation of T and B lymphocytes, natural killer (NK) and lymphokine-activated killer (LAK) cells as well as enhances the activity of natural suppressor cells and macrophages (Novak and Vetvicka 2009).…”
mentioning
confidence: 99%
“…β-Glucans show notable physiological effects; this is their most important quality and the reason why so much attention has been focused on them. Numerous studies (currently more than 5,000 publications) have subsequently shown that β1,3-glucans, either particulate or soluble, exhibits immunostimulating properties, including antibacterial and anti-tumor activities (for review see 3,4 ). In addition to different natural sources, diverse data on the comparison of structure, molecular size, and biological effect can be found in the literature.…”
mentioning
confidence: 99%
“…From the viewpoint of evolution of hominids, to which modern species of man H. sapiens sapiens belong [26], these substances still formed a substantial part of the food of these hunter-gatherers during at least the whole Paleolithic Era. Their health and especially anti-infectious branch of their immunity have been supported principally by β-glucans, which represent important biological response modifiers [27][28][29]. This plant-based diet primarily formed the human genes controlling digestive metabolism and utilizing food components for growth, regeneration and immunity long before the shift to meat-based diets.…”
Section: Paleolithic Dietsmentioning
confidence: 99%